Evaluation of cost-optimal retrofit investment in buildings: the case of Bragança fire station, Portugal - Cova, Sónia; Andrade, Carlos; Soares, Orlando; Lopes, Jorge (International Journal of Strategic Property Management, 2021)
Office buildings built before the entry into force of the first thermal regulation in 1991 constitute a relevant group for analysing the energy performance of the Portuguese building sector. A dynamic energy simulation was used to assess the energy performance of an existing office building located in the town of Bragança, Portugal. Four energy efficiency measures were selected and a financial evaluation through the internal rate of return (IRR) method was undertaken to choose the best retrofit option for improving the building’s energy performance. An investment package consisting of the roof insulation and a new equipment for the domestic hot water system presented an IRR higher than the discount rate used in the analysis, and, thus, a positive financial return. The results of the study also suggest that the EU’s comparative methodology framework is not particularly suitable for assessing building retrofit investment at the private investor’s perspective and further refinement in the cost-effective approach to renovations is needed to help stimulate building’s energy renovation market. Suggestions for further studies conducted for office buildings in the different climate zones in Portugal are also proposed.